Pembekalan Materi Kesehatan Mental Bagi Calon Guru SD di FKIP Universitas Mataram - Kadriyan, Hamsu; Gunawan, Gunawan; Astini, Baik Nilawati; Suranti, Ni Made Yeni; Ibrahim, Ibrahim (Indonesian Journal of Education and Community Services, 2025)
Mental health is a fundamental aspect that prospective teachers must possess to carry out their professional roles effectively. Prospective teachers face various demands that begin in their university years and continue into their future careers as educators. This community service program aims to provide mental health training for elementary teacher candidates at the Faculty of Teacher Training and Education, University of Mataram. The training was conducted in three sessions covering topics such as mental health awareness for teacher candidates, challenges and risks related to teachers’ mental health, creating a safe and supportive classroom environment, self-care for prospective teachers, as well as stress management and resilience. A total of 180 students from semesters 1, 3, and 5 participated in this activity. The implementation methods included material delivery, interactive discussions, video-based learning, and guided reflection. The results indicate that participants gained a better understanding of mental health issues and developed basic skills in managing stress and building resilience. This program is expected to serve as an initial step in fostering mental health awareness and readiness among prospective teachers.